KAJIAN HASIL PELAKSANAAN PELATIHAN PEMBELAJARAN IPA BERBASIS INKUIRI BAGI GURU SEKOLAH DASAR (SD) DI KABUPATEN PONOROGO TAHUN 2018 - Lintang Ratri Prastika; Lukman Nulhakim; Lili Indarti (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2020)
The purpose of this study was to determine the effectiveness of the training and participants' responses to the training. The research was a quasi-experiment with one-group pretest postest design. The sample was chosen using purposive sampling method. The number of samples was 38 elementary school teachers. The research instrument was a test question instrument to determine the effectiveness of the training, and a questionnaire to determine the teacher's response to the training. By using Hake's normalized gain data analysis, a training effectiveness score of 0.40 was obtained, which means that the training was effective enough to increase participants' knowledge related to the training material. While the teacher responses were processed in terms of percentages and graphs, an average of 58.16% of participants rated very well on the training program and an average of 68.95% of participants rated very well on the performance of the facilitator during the training. Based on these results the training carried out has been assessed well by the participants but it is necessary to develop an advanced training program so that the teachers participating in the next training will better understand the inquiry learning model in science learning.